Metagenomic profiling of ocular surface microbiome changes in Demodex blepharitis patients - Fu, Yana; Wu, Jie; Wang, Dandan; Li, Tiankun; Shi, Xinwei; Li, Lu; Zhu, Minying; Zhang, Zuhui; Yu, Xinxin; Dai, Qi (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: To compare the ocular surface and meibum microbial communities of humans with Demodex Blepharitis (DB) and healthy controls. Methods: Conjunctival sac and meibum samples from 25 DB patients and 11 healthy controls were analyzed using metagenomic next-generation sequencing (mNGS). Results: The alpha-diversity of the conjunctival sac microbiome of the DB group (observed, Chao1, ACE) was lower than that of the control group, whereas all meibum diversity indicators were similar. In conjunctival samples, the relative abundance (RA) of the phylum Proteobacteria was significantly higher (p=0.023), and the RA of both phyla Actinobacteria and Firmicutes was significantly lower (p=0.002, 0.025, respectively) in the DB group than that in the control group. In meibum samples, the RA of the phyla Proteobacteria and Actinobacteria were similar, whereas that of the phylum Firmicutes was significantly lower in the DB group (p=0.019) than that in the control group. Linear discriminant analysis with effect size measurement of the conjunctival and meibum microbiomes showed that Sphingobium sp. YG1 and Acinetobacter guillouiae were enriched in the DB group. Sphingobium sp. YG1, Acinetobacter guillouiae and Pseudomonas putida in the DB group were related to more severe ocular surface clinical parameters. Discriminative genera’s principal coordinate analysis separated all control and DB microbiomes into two distinct clusters. Conclusions: Proteobacteria’s increased prevalence may indicate ocular microbial community instability. The species Sphingobium sp. YG1 and Acinetobacter guillouiae are potentially pathogenic bacterial biomarkers in DB. Demodex infection mainly affects the ocular surface microbiome rather than penetrating deeper into the meibomian gland.